Penggunaan Soy wax dan Beeswax sebagai Basis Lilin Aromaterapi: Use of Soy wax and Beeswax as Aromatherapy Candle Base - Theresia Fenny Oktarina; Wisnu Cahyo Prabowo; Angga Cipta Narsa (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
The continuous use of paraffin wax produces pollutants that have a negative impact on health and the environment. Soy wax and beeswax candles are environmentally friendly materials because they produce fewer pollutants. This study aims to determine the best formula in the manufacture of aromatherapy candle preparations. This research was conducted using an experimental method. Aromatherapy candles are made by melting soy wax, beeswax, and stearic acid. Apply optimization based on the ratio formula of 75%:25% (F1), 50%:50% (F2), 25%:75% (F3) by evaluating physical properties such as organoleptic, melting point test, and burning time test to get the base The best aromatherapy candles from the use of soy wax and beeswax ingredients with the addition of stearic acid. The results of optimization of soy wax based on an organoleptic test, F1 and F2 have an even color and do not crack, F3 has an uneven color and does not crack. The melting point of wax preparations is 48°C-52°C, burning time 373 minutes-463 minutes. On the basis of the organoleptic test beeswax, F1 and F2 had an even color and did not crack, F3 had an even color and cracks. The melting point of the basic wax is 53°C-54°C, and the burning time is 443 minutes-499 minutes. From the results, it was found that the best formulas, namely F1 and F2, met the standards according to SNI, namely the color was uniform and not cracked and the melting point ranged from 42°C-60°C.